AN INVESTIGATION ON THE EFFECTIVE PARAMETERS OF LOOSE SANDS LIQUEFACTION POTENTIAL USING IMPROVED HYPERCUBE SAMPLING METHOD - S. Golmoghani Ebrahimi; A. Noorzad; H. Javaheri Koupaei (مهندسی عمران شریف)
The occurrence of the liquefaction phenomenon in saturated loose sandy soils under seismic loads causes the soil particles to tend to decrease in volume. So, if drainage is not possible, the pore water pressure inside the soil increases, and in constant stress conditions, the effective stress between particles approaches zero. In this case, the soil particles have no shear resistance, and liquefaction occurs. Liquefaction is one of the important issues of concern in seismic geotechnical engineering, which involves many uncertainties in soil and earthquake parameters. The most common method to evaluate the potential of liquefaction is a deterministic method, which cannot consider the pertinent uncertainties. Soil properties are uncertain due to various sources of variability of soil deposit formation. Currently, there is a less reliable procedure to account for all pertinent uncertainties in predicting the occurrence of soil liquefaction phenomena when subjected to strong ground motion. In this research, liquefaction reliability analysis was performed by considering the soil and earthquake loading uncertainties using the latest modifications provided by Idris and Boulanger (2014) for the simplified method and using the improved hypercube sampling (IHS) method. Comparing the results of the IHS method with Monte Carlo simulation showed that the proposed method is reliable for liquefaction analysis. The analyses have been performed on well-documented historical cases. The Monte Carlo method has been accepted as the benchmark method in most studies based on liquefaction reliability analysis. Comparison of the Monte Carlo (MC) method and IHS results indicate that the IHS method is more accurate, reliable, and capable than MC for analyzing the reliability of liquefaction and can be used as a benchmark approach in future studies. The results show that the proposed approach is a favorable and useful tool for the reliability analysis of liquefaction potential estimations. Sensitivity analysis based on the coefficient of variation on a wide range of liquefaction and non-liquefaction case histories illustrates that the variability of soil parameters and earthquake loading can affect the probability of liquefaction. It is worth noting that different parameters may have the most effect on the probability of liquefaction depending on soil conditions.